Expression of LYN and PTEN genes in chronic myeloid leukemia and their importance in therapeutic strategy - Ferri, Cristian Alberto (2013)
Tyrosine kinase inhibitors (TKIs), imatinib, nilotinib and dasatinib, are the current treatment of chronic myeloid leukemia (CML). BCR-ABL1 point mutations are the principal cause of resistance to treatment; however other mechanisms could be involved in failure to TKI therapy. LYN is a src kinase protein that regulates survival and responsiveness of tumor cells by a BCR-ABL1 independent mechanism. PTEN tumor suppressor gene is downregulated by BCR-ABL1 in CML stem cells and its deletion is associated with acceleration of disease. In this study we evaluated the expression of LYN, PTEN and the ratio of both genes in 40 healthy donors (HD) and in 139 CML patients; 88 of them resistant to TKI in different phases of disease and 51 in chronic phase classified as optimal responders (OR) to TKI [40 treated with imatinib or nilotinib (OR-IN) and 11 treated with dasatinib (OR-D) therapy]. When we analyzed the gene expression values of LYN, an increase was observed only in advanced stages of the disease, however, when we analyzed the ratio between LYN and PTEN genes, the group of resistant patients in chronic phase in imatinib or nilotinib treatment (CP-IN) also showed a significant increase. Resistant patients treated with dasatinib, a src kinase inhibitor, presented a similar ratio to the observed in HD. In addition, the LYN/PTEN ratio and the LYN expression showed a direct significant correlation with BCR-ABL1 transcript levels in unmutated resistant patients treated with non-src kinase inhibitors. We were able to identify 8/35 (23%) of cases in CP-IN and 4/12 (33%) in accelerated phase and blast phase (AP/BC-IN), in which resistance could be associated with an increase in the ratio of the LYN/PTEN. Our data suggest that the LYN/PTEN expression ratio may be a sensitive monitor of disease progression in unmutated CML patients under imatinib or nilotinib treatment. This ratio could detect cases when resistance is related to altered LYN expression, suggesting that the treatment change to a src kinase inhibitor would be most suitable to overcome resistance.